Kenya: Bungoma country policy brief on land degradation - Kizito, Fred; Tamene, Lulseged D.; Koech, Nicholas; Pondi, Brian; Ng'ang'a, Kennedy (International Center for Tropical Agriculture, 2018)
This policy brief aims to give an overview of land degradation hotspots in Bungoma County and the policy options for land restoration. In this assessment, land degradation is referred to as the persistent loss of ecosystem function and productivity caused by disturbances from which the land cannot recover without human intervention (unaided). Hotspots are defined as places that experience high land degradation and if left unattended, will negatively affect both human wellbeing and the environment. The spatial location of hotspots was identified through a methodology combining modeling, participatory stakeholder consultations and field validation. Understanding the spatial locations helps identify hotspot areas and target them as priority intervention sites with relevant management options. This county policy brief is complemented by detailed National comprehensive assessment report which can be accessed at this link: https://cgspace.cgiar.org/handle/10568/97165